Eine Bau- und Bittinschrift am Tempel von Luxor - Jansen-Winkeln, Karl (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
Republication of an inscription on the outer wall of the forecourt of Amenophis III in the temple of Luxor. The first part of the text is a report on the building of a “Gold House” in the temple of Luxor in year 1 of Alexander the Great. In year 3 of Philip Arrhidaeus, the author of the inscription was promoted chief architect and had to build another Gold House in the temple of Karnak. The exact measures and the time it took to erect both buildings are indicated. In the second part the author prays to Amun to grant him and his eldest son many years, and the priests and scribes of the temple are requested to protect his son. The family of the author’s wife, mentioned in the inscription and known from several other sources, is discussed in conclusion.